Integrated production of Nile tilapia juveniles and lettuce using biofloc technology - Pinho, Sara M. [UNESP]; David, Luiz Henrique C. [UNESP]; Goddek, Simon; Emerenciano, Maurício G. C.; Portella, Maria Célia [UNESP] (Springer Nature, 2021)
The aim of the present study was to evaluate the use of the technology we have named for the first time as FLOCponics (biofloc + hydroponic) (FP) and conventional aquaponics (AP) systems in producing Nile tilapia (Oreochromis niloticus) juveniles and lettuce (Lactuca sativa). The experiment was carried out for 46 days and consisted of two cycles of lettuce production (23 days each) and one cycle of juvenile production. The physical–chemical variables of the water, zootechnical performance of the fish, growth performance and visual characteristics of the plants, nutrient dynamics, and characterization of the planktonic community were evaluated in both systems. The results showed better fish productive performance in FP, with a mean final weight of 36.7 g compared with 34.9 g in AP. For plants, the Cycle 2 in the AP system showed the best plant growth and visual results (98% of the plants received the highest scores—grades A (excellent) and B (good)—on the plant quality index), whereas in FP only 37% achieved these grades in the same cycle. The results suggest that the integrated production of tilapia juveniles and lettuce using FP might be technically feasible if specific fertilization management or mechanisms are developed to refine the critical points of the system (e.g., nutrient imbalance and solids accumulation in the plant roots) to improve plant production.
Keywords: Aquaculture; Aquaponics; FLOCponics; Hydroponic; Nursery